Effect of green manure from Tithonia (T. diversifolia) on the establishment and production of forage of P. purpureum cv. Cuba CT-169 and on some soil properties - Crespo, Gustavo; Ruiz, Tom?s E.; ?lvarez, Julio (Cuban Journal of Agricultural Science, 2011)
In an experimental design of random blocks with four replicates, it was studied the effect of applying three doses of green manure of tithonia (0, 12, and 24 t/ha) on the establishment and production of biomass from P. purpureum cv. Cuba CT-169 forage and on some indicators of red ferrallitic soil. In the first establishment cut, there was no effect of the treatments on the height of the plants. However, the number of tufts/m2 (2.4 ? 2.5), the number of tillers/plant (10.4 ? 10.6), and the DM yield /ha (16.2 ? 18.6 t) were increased significantly in the treatments with green manure, without significant differences between the doses applied. In the second cut (residual effect), conducted three months after the first (February 2009), there were no differences either between treatments for the height of the plants, but the indicators tufts/m2, tillers/plant, and DM yield were increased significantly up to the highest dose of green manure application. The green manure doses reduced significantly (P < 0.01) the apparent soil density (1.01, 0.79, and 0.68 g/cm3 with doses of 0, 12, and 24 t/ha) and increased the contents of OM (4.2%) and N-total (0.30%). The use of T. diversifolia is recommended as green manure to enhance the soil fertility and increase the production of Cuba CT-169 forage on red ferrallitic soil. Key words: T. diversifolia, green manure, forage production, soil.